Genome-Wide Discovery of Single-Nucleotide Polymorphisms and Their Application in Population Genetic Studies in the Endangered Japanese Eel (Anguilla japonica) - Liu, Bing-Jian; Li, Yu-Long; Zhang, Bai-Dong; Liu, Jin-Xian (Frontiers in Marine Science, 2020)
The Japanese eel (Anguilla japonica) is a commercially important aquatic species in East Asia. The number of the Japanese eels has been dramatically declining over the last four decades and it is now listed as an endangered species (ICUN 2014). To manage and conserve this endangered species, it is necessary to assess population genetic diversity, genetic structure, and identify regions of the genome which are under selection. Here, we generated a catalogue of novel SNP markers for the Japanese eel using restriction-site-associated DNA (RAD) sequencing of 24 individuals from two geographic locations. The 73,557 identified SNPs were widely distributed across the draft genome of the Japanese eel. No genetic differentiation between the two populations was detected based on all loci or neutral loci. However, highly significant genetic differentiation was detected based on loci which appeared to be under selection. BLAST2GO annotations of the outlier SNPs yielded hits for 61 (72%) of 85 significant BLASTX matches. KEGG pathway analysis identified some of the putative targets of local selection, including genes in several important pathways such as calcium signaling pathway, intestinal immune network for IgA production and others. This SNP catalogue will provide a valuable resource for future population genetic and genomic studies and allows for targeting speciﬁc genes and genomic regions under selection in the Japanese eel genome.